Formulas for the slowness of Stoneley waves with sliding contact - Giang, P.T.H.; Vįnh, P.C.; Anh, V.T.N. (Archives of Mechanics, 2020)
The main aim of this paper is to derive formulas for the slowness of Stoneley waves traveling along the sliding interface of two isotropic elastic half-spaces. These formulas have been obtained by employing the complex function method. From the derivation of them, it is shown that if a Stoneley wave exists, it is unique. Based on the obtained formulas, it is proved that a Stoneley wave is always possible for two isotropic elastic half-spaces with the same bulk wave velocities. This result leads to the fact that a Stoneley wave is always possible for two elastic half-spaces satisfying the Wiechert condition, a condition that plays an important role in acoustic analyses. The obtained formulas are of theoretical interest and they will be useful in practical applications, especially in nondestructive evaluations.